TERRITORIALIZAÇÃO DA AGROECOLOGIA ENTRE OS AGRICULTORES FAMILIARES NA REGIÃO DO VALE DO RIBEIRA, ESTADO DO PARANÁ - Muterlle, Juliana Carla (2012)
The aim of this dissertation is to analyze the Agroecology territorialization among family farmers in Vale do Ribeira region, Paraná State. For this, it was considered the implementation of Rural Territory , proposed as public policy by the Ministério de Desenvolvimento Agrário (MDA). Development and territory concepts were discussed, supporting the understanding of the Rural Areas formation, in addition to performing analysis of documents provided by MDA. At the same time, semi-structured interviews with farmers, Managing Council of the territory’s members, CRESOL and AOPA’s members were conducted, confronting the lines with one of the objectives listed in this public policy. In other words, the objective to promote the sustainable development of Rural areas, raising the level of wealth and quality of population’s life.Moreover, discussed Agroecology as a contributing element for sustainable development. It was demonstrated how the incentive to transpose a conventional property to a agroecological property considering its principles is intensified by the activities of some ONGs as a AOPA and by Pronaf-Agroecology activities. As a result of the research, the difficulties in materialization of this policy and the difficulties faced by farmers in vale do Ribeira, Paraná State of Paraná were observed. The Agroecology territorialization occurs slowly, because time of transposing from a conventional property to an Agroecological one is relatively long, demanding knowledge and long working